2018
DOI: 10.1016/j.redox.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of mitochondria from airway myeloid-derived regulatory cells to T cells

Abstract: Chronic inflammation involving both innate and adaptive immune cells is implicated in the pathogenesis of asthma. Intercellular communication is essential for driving and resolving inflammatory responses in asthma. Emerging studies suggest that extracellular vesicles (EVs) including exosomes facilitate this process. In this report, we have used a range of approaches to show that EVs contain markers of mitochondria derived from donor cells which are capable of sustaining a membrane potential. Further, we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 76 publications
7
154
0
1
Order By: Relevance
“…For example, mitochondria-embedded exosomes from human HLA-DR þ myeloid-derived regulatory cells can be endocytosed by T cells, in which they remain metabolically active and are integrated into the host mitochondrial network. 123 Brain endothelial cells that endocytose exMTs from endothelial progenitor cells are protected against oxygen-glucose deprivation-induced injury. 124 Macrophages that endocytose exMTs released from mesenchymal stem cells are transformed into highly phagocytic and anti-inflammatory macrophages.…”
Section: Extracellular Mitochondria Disrupt Endothelial Integritymentioning
confidence: 99%
“…For example, mitochondria-embedded exosomes from human HLA-DR þ myeloid-derived regulatory cells can be endocytosed by T cells, in which they remain metabolically active and are integrated into the host mitochondrial network. 123 Brain endothelial cells that endocytose exMTs from endothelial progenitor cells are protected against oxygen-glucose deprivation-induced injury. 124 Macrophages that endocytose exMTs released from mesenchymal stem cells are transformed into highly phagocytic and anti-inflammatory macrophages.…”
Section: Extracellular Mitochondria Disrupt Endothelial Integritymentioning
confidence: 99%
“…Free radical–generating MDRCs are known to regulate activities of T cells and airway responses in asthma (Table ) . While most previous research has focussed on mechanisms of communication through oxidant pathways and soluble mediators, a study by Hough et al have found that exosome‐mediated intercellular transfer could also be a mechanism by which MDRCs in asthmatics can communicate with T cells and signal T cell proliferation. Since mitochondria are capable of secreting ROS and play a role in the inflammatory response, the study aimed to measure mitochondrial transfer in exosomes derived from MDRCs of asthmatics.…”
Section: Resultsmentioning
confidence: 99%
“…23 Exosome could also transfer mitochondria from airway myeloid-derived regulatory cells to T cells, and participate in intercellular communication within the airways of human patients with asthma. 24 Increased secretion of EV-DNA from senescent cells may contribute to age-related chronic inflammation. 25 Besides, under pathological conditions, endogenous RNAs act as DAMPs for pattern recognition receptors (PRRs).…”
Section: Evs and Dampsmentioning
confidence: 99%